(Naqd Al-Maksour) from Fundamentalist’s Point of View - Quteish, Hamzah; Al-Omari, Mahmoud; Al-Qudah, Mousa; Al-Huneiti, Sana (Dirasat: Shari’a and Law Sciences, 2020)
(Al-Kaser) is the cause of (i’llah) from fundamentalist’s point of view, which has two meanings. The first is concerned with the compound work where the objector removes the cause (i’llah) and removes its effect. The second meaning is the failure of judgment on the wisdom. This study is focusing on the first meaning of (Al kaser),which was launched by (Alamidi) and the fundamentalist admired it after that. The study adopted the incomplete extrapolation method, as it is impossible to extrapolate completely, and the incomplete is sufficient for what the research needs, and the comparative method between statements were also used. The study found that there are two meanings of fracture. The first one, who seeks to demolish the compound cause of two descriptions, after he has dismantled it, suggests in the first description that it has no effect and the fundamentalists call it cancellation here, and in the second description the denunciation, and perhaps the closest definition of the fundamentalists is the definition of Al-Sobieski. The second, which seeks to destroy the unilateral cause, for the most part, is a rebuttal, but it responds to wisdom, not to the cause.